Aspirin for secondary prevention of cardiovascular disease in 51 low-, middle-, and high-income countries - Yoo, Sang Gune K.; Chung, Grace S.; Bahendeka, Silver K.; Sibai, Abla M.; Damasceno, Albertino; Farzadfar, Farshad; Rohloff, Peter; Houehanou, Corine; Norov, Bolormaa; Karki, Khem B.; Azangou-Khyavy, Mohammadreza; Marcus, Maja E.; et al. (The journal of the American Medical Association, 2023)
OBJECTIVE To report and evaluate aspirin use for secondary prevention of CVD across low-, middle-, and high-income countries. DESIGN, SETTING, AND PARTICIPANTS Cross-sectional analysis using pooled, individual participant data from nationally representative health surveys conducted between 2013 and 2020 in 51 low-, middle-, and high-income countries. Included surveys contained data on self-reported history of CVD and aspirin use. The sample of participants included nonpregnant adults aged 40 to 69 years. EXPOSURES Countries’ per capita income levels and world region; individuals’ socioeconomic demographics. MAIN OUTCOMES AND MEASURES Self-reported use of aspirin for secondary prevention of CVD. - RESULTS The overall pooled sample included 124 505 individuals. The median age was 52 (IQR, 45-59) years, and 50.5% (95% CI, 49.9%-51.1%) were women. A total of 10 589 individuals had a self-reported history of CVD (8.2% [95% CI, 7.7%-8.6%]). Among individuals with a history of CVD, aspirin use for secondary prevention in the overall pooled sample was 40.3% (95% CI, 37.6%-43.0%). By income group, estimates were 16.6% (95% CI, 12.4%-21.9%) in low-income countries, 24.5% (95% CI, 20.8%-28.6%) in lower-middleincome countries, 51.1% (95% CI, 48.2%-54.0%) in upper-middle-income countries, and 65.0% (95% CI, 59.1%-70.4%) in high-income countries. - CONCLUSION AND RELEVANCE Worldwide, aspirin is underused in secondary prevention, particularly in low-income countries. National health policies and health systems must develop, implement, and evaluate strategies to promote aspirin therapy.